Editors' introduction: Since last We spoke…. Issue 3 (2nd July 2020) - McCandless, Sean; Zavattaro, Staci M.
Abstract: As Administrative Theory & Praxis's Dialogues series on COVID-19 continues, we reflect on where we have come and where we are going while previewing new pieces in the series.